PENGARUH PROGRAM PEMUTIHAN PAJAK, PEMBEBASAN BEA BALIK NAMA, SOSIALISASI DAN KESADARAN WAJIB PAJAK TERHADAP KEPATUHAN PAJAK KENDARAAN BERMOTOR - Fadlun Adnan, Najwa; Dara , Amin; Abu, Zulkifli (Jurnal Ilmiah Akuntansi dan Keuangan (JIAKu), 2025)
The objectives of this study were: (1) to analyze whether the influence of the motor vehicle tax bleaching program on the compliance of motor vehicle taxpayers (2) to analyze whether the exemption of motor vehicle title transfer fees affects the compliance of motor vehicle taxpayers (3) to analyze whether taxation socialization affects the compliance of motor vehicle taxpayers (4) to analyze whether taxpayer awareness affects the compliance of motor vehicle taxpayers. This type of research is quantitative research. The analysis model used in this research is multiple linear analysis using SPSS 26. Based on the results of the study, it shows that (1) the motor vehicle tax bleaching program has no significant effect on taxpayer compliance (2) exemption of motor vehicle title transfer fees has a positive and significant effect on motor vehicle taxpayer compliance (3) tax socialization has no effect with a negative relationship direction is not significant (4) taxpayer awareness has a positive and significant effect on motor vehicle taxpayer compliance